Brief mindfulness coaching enhances selective attention in medical scientists: A pilot study - Satish Jaiswal; Jason Nan; Suzanna R. Purpura; James K. Manchanda; Iris Garcia-pak; Dhakshin S. Ramanathan; Dawna Chuss; Deborah T. Rana; Ellen Beck; Paul A. Insel; Neil C. Chi; David M. Roth; et al. (PLoS ONE, 2025)
Medical scientists have dual commitments to clinical care and research efforts. Such commitments can create hectic and stressful work schedules, which may impact on well-being and cognition. In this study, we tested the hypothesis that brief mindfulness coaching (three 1.5 hour online group sessions over 12 weeks) can benefit medical scientists. We conducted a waitlist-controlled intervention study (n = 43) with M.D./Ph.D. preclinical or graduate students and post M.D./Ph.D. trainees/faculty. Assessments of quantitative outcomes included self-reports of burnout, mindfulness, self-compassion, and well-being, as well as objective neuro-cognitive assessments. The results showed no effect of intervention on self-report measures. However, amongst cognitive measures, selective attention performance was significantly improved following the intervention (bias corrected effect size, Hedges’ g = 1.13, p = 0.005). Extent of improvement in selective attention correlated with suppression of visual alpha oscillations – a neural marker for distractibility – measured using electroencephalography (EEG) (r = −0.32, p < 0.05). Qualitative feedback showed that after receiving the intervention, participants in both study arms equally rated the overall experience as “very good” (3.70 ± 0.98 out 5). They also appreciated that the intervention emphasized healthy lifestyle behaviors, and contributed to mindfulness, compassion, and a sense of community. A majority (57%) of the participants reported that they expect to change their well-being related behaviors because of the intervention. Overall, this study suggests the utility of brief mindfulness coaching to improve selective attention skills in medical scientists and that more needs to be done to enhance subjective well-being in this healthcare workforce. Trial registration: The study was registered in the International Standard Randomized Controlled Trial Number Registry (ISRCTN16736293) at https://www.isrctn.com/.